2019
DOI: 10.1186/s40662-019-0165-y
|View full text |Cite
|
Sign up to set email alerts
|

Central corneal regularization (CCR): an alternative approach in keratoconus treatment

Abstract: BackgroundTo evaluate the safety and efficacy of an approach that combines corneal customized transepithelial therapeutic ablation to treat irregular corneal optics and accelerated corneal collagen cross-linking (CXL) to strengthen the corneal tissue and stop the progression of keratoconus. The transepithelial therapeutic ablation applied a novel concept named central corneal regularization (CCR) which could correct the corneal morphological irregularities and the eye’s spherocylindrical refractive error with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 21 publications
2
22
0
Order By: Relevance
“…Thereby, granting a constant radial slope to minimize and homogenize the risk of regression in radial direction induced by epithelial regrowth, the observed stability in our cohort may be more solid compared to other PRK techniques. 35 However, a longer follow-up time could report a certain amount of regression in our cohort.…”
Section: Discussionmentioning
confidence: 67%
“…Thereby, granting a constant radial slope to minimize and homogenize the risk of regression in radial direction induced by epithelial regrowth, the observed stability in our cohort may be more solid compared to other PRK techniques. 35 However, a longer follow-up time could report a certain amount of regression in our cohort.…”
Section: Discussionmentioning
confidence: 67%
“…This preliminary study presents some limitations, such as a low number of eyes and short postoperative follow-up time, so we hope that future studies with larger study cohorts will confirm these preliminary findings since every step forward we take in improving the safety and efficacy of our procedures is positive. After further studies, a possible new scenario of application of this solution could be in CXL plus treatments with sequential and simultaneous Customized Trans-Epithelial No-touch (cTen ® ) photo-ablation, corneal shape remodeling for the reduction of total high order aberrations through a specific customized interactive iVis Technologies proprietary software (CIPTA ® ) [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a protocol in the name of "Central Corneal Regularization (CCR)" on the iVis Suite customized excimer laser ablation treatment platform (iVis Technologies S. r. l., Taranto, Italy) was tried with keratoconus patients (Amsler-Krumeich stage I-II) and was shown to improve both uncorrected and corrected visual acuity. 71,72 A subsequent comparative study also showed that the combination of the CCR/PRK approach with C-CXL results in a more effective reduction in higher-order aberrations and Kmax than what can be achieved with C-CXL alone. 73 Kanellopoulos AJ modified the Athens protocol by incorporating topographically guided varied pattern C-CXL into the protocol thereby reducing the amount of tissue that has to be removed by PRK.…”
Section: Advances In Treatmentmentioning
confidence: 98%